Describing The ELE Fresh Graduate Students’ Habit of Listening to English Songs and Listening Self-Efficacy - Fadly, Firlyano; Anugerahwati, Mirjam (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2023)
Listening is one of the essential language skills, but previous research has shown that listening is one of the most difficult language skills to acquire. There are two main factors that can cause problems when learning listening skills, there are external and internal. Self-efficacy is one of the internal factors. On the other hand, English songs are said to be an effective medium for students to learn listening skills. The purpose of this study is to describe the ELE fresh graduate student’s habit of listening to English songs and their listening self-efficacy. The study is using descriptive study, there are 40 participants, and the researcher used a questionnaire and in-depth interviews to collect the data. The research showed that there is positive result from participants’ habit of listening to English songs and their listening self-efficacy. There are some main factors of English songs that help students to improve their listening, namely the lyrics, the exposure of new vocabulary, and the positive effect on students’ mood.